Strategi Pengembangan Pariwisata Kebun Raya Mangrove Gunung Anyar dalam Meningkatkan Keberlanjutan Ekosistem dan Ekonomi UKM Surabaya Jawa Timur - Devita Tyas Ayu Firnanda (Lembaga Pengembangan Kinerja Dosen, 2025)
The strategy of developing tourism in Gunung Anyar Mangrove Botanical Garden in improving the sustainability of the ecosystem and the economy of SMEs in Surabaya, East Java has been carried out well by the mangrove tourism manager. The manager of the Gunung Anyar Mangrove Botanical Garden continues to make efforts to develop the area sustainably, including by increasing the diversity of the mangrove ecosystem and empowering Micro, Small and Medium Enterprises (MSMEs) who are active in tourism activities. This study examines the strategies implemented in the management of the Gunung Anyar Mangrove Botanical Garden, especially related to the preservation of the mangrove ecosystem and the role of MSMEs in attracting visitors. The purpose of this study was to identify the strategy for developing the tourism ecosystem in the Gunung Anyar Mangrove Botanical Garden in the future and to analyze the role of MSMEs in increasing the number of tourists visiting their business locations. The results of the study showed that the strategy for developing tourism in the Gunung Anyar Mangrove Botanical Garden utilizes the advantages it has to maximize existing opportunities, while overcoming shortcomings and facing emerging challenges in order to support the sustainability of the mangrove ecosystem and increasing the role of MSMEs in attracting tourists.